Using Photography to Capture Young People's Views About Community and Local Service Delivery. Issue 3 (3rd July 2022) - Savuro, Nikkola; Gair, Susan; Braidwood, Lilli; D'Emden, Cindy; O'Reilly, Sara; Walsh, Emma; Zuchowski, Ines
ABSTRACT: Youth offending has received significant attention in recent years in Queensland and across Australia. While the voices of young people who are offending or at risk of offending are evident in some studies, other reports do not identify them as key stakeholders. A recent university–industry research collaboration sought to prioritise the voices of young people engaging with The Lighthouse, a diversionary service within Townsville Aboriginal and Islander Heath Services (TAIHS), through the use of qualitative, photovoice methods. The primary aim of this photovoice project was to capture the perceptions and needs of young people currently at risk of offending in order to help shape local service delivery. A thematic analysis enabled the identification of four key themes. Participants felt unsafe and under surveillance in public spaces; they wanted more amenities where they could enjoy being in the community with their peers; they reported that peers and family were very important to them; and they appreciated services on offer at The Lighthouse and acknowledged these services supported behavioural change. The findings provide a unique contribution to policy and service delivery focused on young people at risk of offending and to the literature on the use of photovoice methodologies. IMPLICATIONS Photovoice is a creative, participatory method that value adds to research outcomes through participant skill development. Young people participating in, or at risk of, offending can contribute to research, in turn informing policy and practice to better meet their needs. Seeing through the eyes of young people provides a unique perspective on community inclusion, safe spaces, and transformative practice.